Dietary Fiber in Sour Cream Products - Dolmatova O.; Doshina A. (Техника и технология пищевых производств)
The consumption of sour cream in Russia is growing every year. According to the data obtained from the Federal State Statistics Service and the Federal Customs Service, the production volume of sour cream in Russia in-creased by 5.55% in 2014–2018. However, the production of sour cream remains lower than its consumption. The solu-tion may be in production of sour cream products, which will make it possible to satisfy the demand, while non-dairy components will make the products functional. The authors propose to use fiber as a functional ingredient. The present research featured sour cream, a sour cream product with a 20% fat content, and such components of plant origin as fiber of Vitaminaya Polyana brand, rye fiber, wheat fiber, wheat fiber with licorice, and carrot puree. The authors selected the most optimal formula and composition for sour cream products. Standard research methods were used to study the sensory, physical, chemical, and microbiological indicators of the dairy products. The experiment revealed that 2.5% of fiber in the composition of sour cream product improved its consumer properties while preserving the original taste and smell of the product. Carrot puree was used as a color correcting and flavoring component. Its dosage was determined empirically. The sample of sour cream product with a carrot puree fraction of 5.0% received the highest overall rating. Fortified sourcream was obtained according to the technological scheme of production of sour cream with the addition of non-dairy components at the standardizing stage. The samples of sour cream product with fiber were found to promptly restore its structure and were characterized by an increased viscosity index compared with the control sample. The research resulted in a sour cream product with wheat fiber, licorice, and carrot puree. Samples of sour cream products and sour cream were stored for 20 days at a temperature of 6 ± 2 °C. The study established the optimal shelf life as 14 days.